Ecomodernity as a Cultural Programme: Combining Green Transition with an Educational Paradigm Shift. Issue 1 (2nd January 2016) - Witoszek, Nina
Abstract : This paper conceptualizes the diverse responses and solutions to the environmental and climate crisis as a battle of modernities, where a well-entrenched and efficient 'carbon modernity' is increasingly challenged by alternative visions of social well-being and industrial development. This 'battle' shows that, although the twenty-first century's scenarios of a sustainable future may vary, the common rallying cry is most often for the mobilization of modernity's innovative potential to get the planet out of its current predicament, and less so the idea of a return to a Spartan, pre-modern nature-utopia. There is now a plethora of concepts describing the greening of modernity, from 'sustainable development', 'ecological modernization', 'green growth' and 'transformation' to the 'post-growth', 'no-growth' or even ' de- growth' economy. The paper contends that it is time to put these concepts – and their accompanying practices – into dialogue with one another and imbue them with an overarching cultural objective. The suggested concept of 'ecomodernity' reconciles the modernity of the Enlightenment with a return to oikos – the ancient concept of the more-than-human 'household' or 'natural home' – reclaiming the discarded connection between humans and nature. The paper drafts the cultural contours of ecomodernity in terms of a pivotal paradigm shift in education, which involves redefining human identity, reimagining the balance between competition and cooperation, and supplementing knowledge with wisdom.